2003
DOI: 10.1128/jvi.77.19.10270-10279.2003
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Microtubule Cytoskeleton and Dynein during Parvoviral Traffic toward the Nucleus

Abstract: Canine parvovirus (CPV), a model virus for the study of parvoviral entry, enters host cells by receptormediated endocytosis, escapes from endosomal vesicles to the cytosol, and then replicates in the nucleus. We examined the role of the microtubule (MT)-mediated cytoplasmic trafficking of viral particles toward the nucleus. Immunofluorescence and immunoelectron microscopy showed that capsids were transported through the cytoplasm into the nucleus after cytoplasmic microinjection but that in the presence of MT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 64 publications
7
82
0
Order By: Relevance
“…[22][23][24][25][26] In these studies, significant accumulation of viral particles near the nucleus was seen within 1-2 h. The actin network can also act as a transport conduit, as demonstrated by bacculovirus, which uses the actin network exclusively for transport, 27 and HIV, which uses both actin and microtubule networks for cytoplasmic trafficking. 22 Nonviral vectors, depending on their mode of transfection, can also use cytoskeletal machinery to travel toward the nucleus.…”
Section: The Percent Of Apoptotic Cells (7sd) Is Shownmentioning
confidence: 79%
“…[22][23][24][25][26] In these studies, significant accumulation of viral particles near the nucleus was seen within 1-2 h. The actin network can also act as a transport conduit, as demonstrated by bacculovirus, which uses the actin network exclusively for transport, 27 and HIV, which uses both actin and microtubule networks for cytoplasmic trafficking. 22 Nonviral vectors, depending on their mode of transfection, can also use cytoskeletal machinery to travel toward the nucleus.…”
Section: The Percent Of Apoptotic Cells (7sd) Is Shownmentioning
confidence: 79%
“…Many animal viruses rely on microtubule-based transport for delivery to the nuclear envelope, where the viral genome is released through the nuclear pores (29,30). Salman et al (23) demonstrated integration of the microtubule delivery and nucleocytoplasmic transport systems in an animal cell model, showing that the same NLS responsible for translocation through nuclear pores also invoked active, dyneinmediated transport along microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…170 Numerous viruses have taken advantage of this intracellular transport system and utilize dynein-mediated trafficking to catch a ride to nuclear periphery. [171][172][173][174][175][176] While in some cases intact cytoskeletal elements are Intracellular trafficking of nonviral vectors LK Medina-Kauwe et al required for appropriate nonviral vector trafficking in cells, in other cases, the cytoskeleton may either interfere with intracellular translocation or direct nonviral vectors to undesirable sites within the cell. In many of the studies mentioned earlier, the contribution of the cytoskeleton to vector uptake and vesicle trafficking was described.…”
Section: Cytoskeletal Factorsmentioning
confidence: 99%